Analysis of the legionnaires' risk water facilities in the sun coast of Malaga, Spain - Gea Izquierdo, Enrique (2008)
In Spain, during the last decade, it has increased the interest by the preventive- hygienic maintenance for the microbiological control in the water facilities. Some protocols of treatment and norms have been developed to obtain an optimal quality in the parameters of the air- water interchange facilities. Diverse investigations have shown the existence of Legionella pneumophila biological agent. The study approaches the application of preventive maintenance methods with object to control the bacterium development. A water facilities sample corresponding to public buildings from the Coast of the Sun (Málaga, Spain) was investigated, by means of 83 variables, cluster and correspondences analysis. The results include a detailed analysis of the water quality control application methods according to the types of buildings. It concludes with the maintenance fulfillment degree and the importance corresponding to each typology.